Penerapan Internet Of Things Pada Sistem Monitoring Pembangkit Hibrida - Ilham Ramadhan; Dian Budhi Santoso (Peneliti.net, 2022)
Renewable energy is energy that comes from nature and can be used freely. This energy can be used as a power generation system, One example of the use of renewable energy is by making Hybrid Power Plant (PLTH). Hybrid Power Plant (PLTH) is a power plant consisting of at least 2 generators with various sources of energy. For example, in this study using a combination of a solar power plant (PLTS) with a generator Wind Power (PLTB). This PLTH is designed using 2 units 100WP solar panels and a vertical 300W wind turbine which will deliver the energy produced by PLTH to the battery as a power supply. To prevent the occurrence of damage and decreased performance on the PLTH system and battery, an Internet- Of Things (IOT) to monitor performance when system performance decreases so that it can be anticipated so that no damage occurs. In this research, used a Voltage sensor (Voltage Divider), Current Sensor (ACS712), Sensor Current (MAX471), Wind Speed ​​Sensor (Anemometer), Light intensity sensor (BH1750) and the Kodular platform as an application platform featuring sensor readings. Research begins with designing software and circuit hardware to test the success of the system, then design Kodular platform, as well as designing programs using software Arduino IDEs. In sending data using internet media, it is used wi-fi module (ESP32) to send arduino readings to webserver firebase with JSON program. Results obtained from sensor testing voltage and current sensors have a percentage difference with the measuring instrument, namely less than 3% this indicates that the sensor used can still be used work well. Keywords: PLTH, Sensor, IOT, Arduino, Solar Panel, Wind Turbine